Application Of Photodynamic Therapy With Magnetic Fields And Dyes For The Treatment Of Microbial Skin Infections In Vitro And In Vivo - Al-Dalawi, Ali Adil Turki (2024)
This study aims to explore the multifaceted approach that these qualities provide to the mechanism of action of aPDT in both in vitro and in vivo settings. Initially, the study focuses on determining the depths of penetration and transmission of laser light at various wavelengths across diverse tissues in vitro.